Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1126/science.1190187
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Activation of Class Ib Ribonucleotide Reductase

Abstract: The class Ib ribonucleotide reductase of Escherichia coli can initiate reduction of nucleotides to deoxynucleotides with either a MnIII2-tyrosyl radical (Y•) or a FeIII2-Y• cofactor in the NrdF subunit. Whereas FeIII2-Y• can self-assemble from FeII2-NrdF and O2, activation of MnII2-NrdF requires a reduced flavoprotein, NrdI, proposed to form the oxidant for cofactor assembly by reduction of O2. The crystal structures reported here of E. coli MnII2-NrdF and FeII2-NrdF reveal different coordination environments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
251
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(276 citation statements)
references
References 25 publications
16
251
1
Order By: Relevance
“…Participation of the loop in an extended ␤-sheet hydrogen-bonding pattern prevents the 70s loop backbone from interacting directly with the FMN cofactor in the oxidized state. This feature is distinct from what is observed in the E. coli NrdI ox structure in which the corresponding loop is flexible and glycine-rich, allowing for hydrogen bonding interactions with the N5 of the FMN via a backbone amide NH (15). The short loop (XFG) in the Bacillus NrdIs is similar to S. sanguinis NrdI ox in that neither can form this interaction.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 76%
See 1 more Smart Citation
“…Participation of the loop in an extended ␤-sheet hydrogen-bonding pattern prevents the 70s loop backbone from interacting directly with the FMN cofactor in the oxidized state. This feature is distinct from what is observed in the E. coli NrdI ox structure in which the corresponding loop is flexible and glycine-rich, allowing for hydrogen bonding interactions with the N5 of the FMN via a backbone amide NH (15). The short loop (XFG) in the Bacillus NrdIs is similar to S. sanguinis NrdI ox in that neither can form this interaction.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 76%
“…The short loop (XFG) in the Bacillus NrdIs is similar to S. sanguinis NrdI ox in that neither can form this interaction. The Bacillus and E. coli NrdIs have also been structurally characterized in the sq-or hq-reduced states (15,50,51). All of these structures reveal a backbone amide flip that positions a carbonyl group near the N5 position to interact with the now protonated form of the cofactor.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 99%
“…Extensive investigations on the Ct enzyme have revealed that a Mn(IV)Fe(III) site, as formed after O 2 reduction at divalent manganese and iron ions, is the target of the proton-coupled electron transfer from R1 (25)(26)(27)(28)(29)(30). Also in CtR2 under certain conditions an FeFe cofactor can be incorporated, but shows significantly lower activity (31,32).…”
mentioning
confidence: 99%
“…Class Ib RNR is reduced by NrdHredoxin or thioredoxin (8 -11). NrdH-redoxins are small glutaredoxin-like proteins often coded within the same operon as nrdE and nrdF, the two subunits of the class Ib RNR (12). They have a sequence identity in the range of 35-85% with glutaredoxins (Grx) but receive electrons from thioredoxin reductase (TrxR) (10).…”
mentioning
confidence: 99%
“…Class I RNRs are oxygen-dependent enzymes containing a di-iron cluster (2). Oxygen-independent class II enzymes have a cobalamin cofactor (vitamin B 12 ), whereas the activity of oxygen-sensitive class III RNRs depends on an iron-sulfur cluster (3)(4)(5). Class I RNRs are further divided into class Ia (NrdAB) and Ib (NrdEF); class Ia is present in eukaryotes, prokaryotes, and viruses, whereas class Ib is only found in prokaryotes (6).…”
mentioning
confidence: 99%